AGAMA DAN PEMBANGUNAN EKONOMI REGIONAL DI BANTEN TAHUN 2000-2016 - Khusaini Khusaini; Heni Cahya Ramdani; Hebi Ardi Safira (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
This study aims to determine the condition of the economy and the influence of culture and regional economic development in Banten. This research was conducted in Banten using secondary data for the period of 2000 - 2016?? taken from the Central Bureau of Statistics and other agencies related to this research. The research method was correlational quantitative. Variables are used consits of economic development, religious, and agricultural development as its variables. Religion uses indicator of the number of Muslim population. The results show that partially, agricultural development affects economic development but there is no influence of religion on economic development. And simultaneously shows that there is influence between religion and agricultural development on economic development in Banten 2000-2016.